Effect of monensin on the specific activity of ammonia production by ruminal bacteria and disappearance of amino nitrogen from the rumen. - Yang, C M (1993)
When unadapted mixed ruminal bacteria (312 mg of protein per liter) were treated with monensin (5 mM) in vitro, the rates of ammonia production from enzymatic digests of casein, gelatin, and soy protein (0.5 g of N per liter) were decreased from 46 +/- 2 to 24 +/- 1, 20 +/- 1 to 7 +/- 1, and 40 +/- 2 to 18 +/- 2 nmol/mg of protein per min, respectively. Monensin also caused a decrease in ammonia production in vivo. Nonlactating dairy cows which were fed 0.56 kg of timothy hay 12 times per day had a steady-state ruminal ammonia concentration of 2.7 +/- 0.1 mM, and the ammonia concentration decreased to 1.2 +/- 0.2 mM when monensin (350 mg/day) was added to the diet. The decrease in ammonia production was associated with a 10-fold reduction (4.1 x 10(6) versus 4.2 x 10(5)/ml) in the most probable number of ammonia-producing ruminal bacteria that could use protein hydrolysate as an energy source. Monensin had little effect on the most probable number of carbohydrate-utilizing ruminal bacteria (6.5 versus 7.0 x 10(8)/ml). The addition of protein hydrolysates (560 g) to the rumen caused a rapid increase in the ammonia concentration, but this increase was at least 30% lower when the animals were fed monensin.(ABSTRACT TRUNCATED AT 250 WORDS)